'Pussy Panic' and Glass Elevators: How Gender is Shaping the Field of Animal Studies. Issue 100 (3rd April 2019) - Probyn-Rapsey, Fiona; O'Sullivan, Siobhan; Watt, Yvette
ABSTRACT: The 'pussy panic' of our title is a phrase that belongs to Susan Fraiman. It is a diagnosis, a lament, and a warning about how Animal Studies (AS) is currently torn between rising academic respectability bestowed through the 'installation of Derrida as founding father', and the neglect that this entails for AS's deep roots in feminist scholarship going back decades, and across a number of disciplines. Finding that a 'proximity to this feminized realm' of 'siding with animals' can bring about a 'pussy panic' in male scholars, Fraiman draws a parallel between academic mainstreaming and the suppression of the 'emotionally and politically engaged' work of earlier feminist writers (93). Inspired by Fraiman's reading and her sense of a lingering pussy panic in the field of AS, we were interested to inquire whether or not the academic legitimacy the field deserves has also brought with it a privileging of men's voices as it has developed over the years. We conducted a large, broad-ranging international survey of AS scholars. From that larger survey, the issue of gender stood out and enabled us to investigate Fraiman's observations further. Our data lend support to the idea that 'pussy panic' has indeed shaped the direction of the field so far.